2020
DOI: 10.1007/s40305-020-00295-9
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Introduction to Manifold Optimization

Abstract: Manifold optimization is ubiquitous in computational and applied mathematics, statistics, engineering, machine learning, physics, chemistry and etc. One of the main challenges usually is the non-convexity of the manifold constraints. By utilizing the geometry of manifold, a large class of constrained optimization problems can be viewed as unconstrained optimization problems on manifold. From this perspective, intrinsic structures, optimality conditions and numerical algorithms for manifold optimization are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(77 citation statements)
references
References 107 publications
(175 reference statements)
0
77
0
Order By: Relevance
“…By viewing the sphere M as a single nonlinear equality constraint, the classical methods for nonlinear programming (see e.g., [17] and the Matlab routine fmincon) can be used for solving (1.2). Viewing M as a simple embedded sub-manifold of R n , the recent developments on the manifold optimization (e.g., [1,7,10,11,25]) provide other efficient ways for (1.2). In particular, the Riemannian trust-region (RTR) method we used in Example 3.1 extends the classical well-known trust-region method (see e.g., [17,Chapter 4]) to a general Riemannian manifold.…”
Section: Algorithmsmentioning
confidence: 99%
“…By viewing the sphere M as a single nonlinear equality constraint, the classical methods for nonlinear programming (see e.g., [17] and the Matlab routine fmincon) can be used for solving (1.2). Viewing M as a simple embedded sub-manifold of R n , the recent developments on the manifold optimization (e.g., [1,7,10,11,25]) provide other efficient ways for (1.2). In particular, the Riemannian trust-region (RTR) method we used in Example 3.1 extends the classical well-known trust-region method (see e.g., [17,Chapter 4]) to a general Riemannian manifold.…”
Section: Algorithmsmentioning
confidence: 99%
“…In this section, we apply manifold optimization technique to obtain a sub-optimal solution of the above problem (16). The background on manifold optimization is illustrated in [57]- [59]. Also, application of this algorithm can be found in [60].…”
Section: Design Of Analog Precodermentioning
confidence: 99%
“…where sym(M) denotes the symmetric part of M, i.e., sym(M): � ((M + M T )/2). We next introduce several different retraction operators on the Stiefel manifold at the current point X for a given step size t and descent direction ξ (one can refer to [27] for more details).…”
Section: Preliminariesmentioning
confidence: 99%
“…Numerical experiments and comparisons with other state-ofthe-art methods indicated that their proposed algorithm is very promising. Another popular second-order algorithm on Stiefel manifold is the Riemannian trust-region (RTR) algorithm [24][25][26][27][28], which has been successfully applied to various applications. In particular, Yang et al [29] presented the RTR algorithm for H 2 model reduction of bilinear systems, where the H 2 error norm is treated as a cost function on the Stiefel manifold.…”
Section: Introductionmentioning
confidence: 99%